Analysis of Right to Rest & Leisure among Migrant Construction Worker - C Janarthan; Dr. Ahrar Ahmad Lone, (Indian Journal of Social Science and Literature (IJSSL), 2025)
Throughout his lengthy career, the author has worked with migrant construction workers and has seen firsthand the many issues they encounter, including ongoing Right to Rest and Leisure. Consequently, he was compelled to meticulously investigate their plight after retiring and doing his doctoral studies on the hardships & human rights violations of migrant construction workers. It is believed that a systematic sociological analysis of the situation regarding the Right to Rest and Leisure is necessary to bring it to the consideration of policymakers. The problems faced by migrant construction workers are a concern of social relevance that requires the attention of all concerned for the well-being of workers and the development of society. This article reviews the outcomes of earlier field studies and examines relevant national and international laws and acts through a literature review. He further analysed the Right to Rest and Leisure in earlier studies, drawing on his long personal experience and the outcome of observational research conducted by him in Labour Chowk, Greater Noida, India. Migrated construction workers experience numerous health problems due to improper rest and Leisure, constituting a significant life stressor. These are positively correlated with illnesses, according to several studies. Previous research indicates that human rights abuses, especially those related to the Right to Rest and Leisure, continue despite measures outlined in the Indian Constitution, international treaties, and the country's efforts. At the end of the article, the Author also identified specific suggestions based on the analysis for the wellness advocacy of Migrant Construction Workers.